Utilization of Oocytes Collected from Preserved Ovarian for In Vitro Production of Cat Embryos - Kartini Eriani; Arief Boediono; Sony Heru Sumarsono; Al Azhar (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Preservation of ovarian tissue from severely injured or dead valuable animals has the potential to preserve female germ cells of animals. The ability to mature and fertilize of oocytes from preserved ovary of endangered species will allow us to sustain genetic and global biodiversities. The aims of this study were to investigate the viability of oocytes collected from the preserved ovary and its potential utilization for the production of cat embryos followed by in vitro maturation and fertilization. Ovary was preserved immediately in phosphate buffer saline (PBS) at 4 Â°C for 24 or 48 hours. The quality and viability of oocytes after the maturation process were identified microscopically using aceto-orcein staining. Biological function of the oocytes was evaluated by using in vitro culture technique for the maturation and fertilization rate in CR1aa medium culture. The results showed that the percentage of oocytes collected from preserved ovary for 24 and 48 hours that remained at the stage of metaphase-II were 29.4% and 21.9% respectively. Fertilization rates produced in the IVF using oocytes collected from ovary preserved for 24 or 48 hours were significantly lower (30%) than that of unpreserved control (36.7%). In conclusion, female germ cells of cat ovary preserved at 4 Â°C in PBS for 2 days were still viable for in vitro fertilization and thus can be utilized for in vitro production of cat embryos. Information obtained can be used as a basis of knowledge of using a combination of physiological reagent and cold-based preservation technique in modern reproductive technology for animals.